Internet business strategies by property companies in Asia - Razali, Muhammad Najib; Manaf, Zaharah; Mohd Yassin, Azlina (Emerald, 2010)
Purpose – The purpose of this paper is to present the results of a study of the top listed property companies in Asia based on capital market value on internet business strategy, and to examine the relationship between top companies and the internet business strategy index. Design/methodology/approach – Data for the research were collected from the top 30 property companies in Asia through their web sites. The services and information offered in these web sites are discussed and used to describe the growth of internet usage in the real estate business. Findings – From the findings, most companies in Asia realised the importance of the internet as a marketing tool. This has been proved from the good average score of the internet business strategy attributes. The results indicated that top property companies in Asia implemented good internet business strategy. Research limitations – The research is based on a study from the top 30 companies in Asia based on market capital values as at 30 June 2009. Only three countries were selected in this study: Malaysia, Singapore and Hong Kong. Originality/value – This paper examines the practice of property companies in Asia of using the internet as a marketing tool in property business in order to enhance the marketing strategy in this borderless world. The findings provided some insight and guidelines for the industry as well as academics on the use of information and communication technology in the property business.